Enhancing loyalty in Islamic hospitals: Exploring customer experience as mediating variables - Purnama, Chamdan; Rahmah, Mirhamida; Fatmah, Dinda; Hasani, Syaiful; Rahmah, Yusriyah; Rahmah, Zakiyah Zulfa; Mulyono, Sugeng; Anam, Chairul (Center for Islamic Economics and Development Studies [P3EI], 2024)
Purpose – This study investigates the impact of service quality and corporate image on customer experience and loyalty within health institutions.Methodology – Utilizing a correlation research design, data were collected from 80 hospital patients using a purposive sampling technique. Data were analyzed using regression analysis in SPSS version 25.Findings – The findings reveal that Service quality and corporate image significantly enhance customer experience. Moreover, while service quality directly influences loyalty, the impact of corporate image on loyalty is mediated by customer experience.Implications – The study suggests Hospitals should focus on improving service efficiency, communication, and patient satisfaction in order to strengthen patient loyalty. Additionally, cultivating a positive corporate image through patient interactions can further enhance the customer experience, leading to increased loyalty. Originality – This study introduces a novel conceptual model that integrates customer experience as a mediating variable to explain loyalty dynamics in health institutions. This study's contributions are particularly relevant for hospital management, although the relatively small sample size may limit the broader applicability of the results.